2018
DOI: 10.1002/jcb.27496
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase, RhoA, and p38 mitogen‐activated protein kinase modulates apoptosis mediated by angiotensin II AT2 receptors

Abstract: Apoptosis plays an important role in cellular processes such as development, differentiation, and homeostasis. Although the participation of angiotensin II (Ang II) AT receptors (AT R) in cellular apoptosis is well accepted, the signaling pathway involved in this process is not well established. We evaluated the participation of signaling proteins focal adhesion kinase (FAK), RhoA, and p38 mitogen-activated protein kinase (p38MAPK) in apoptosis induced by Ang II via AT R overexpressed in HeLa cells. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Recently, Yan et al (36) demonstrated that the application of Y27632 promoted the gene expression of matrix metalloproteinases 2/3 and Notch-1 signaling to modulate Yes-associated protein-1 localization in the regulation of efficient patterning of cardiovascular spheroids following mesoderm formation from hPSC. Therefore, the possibility that ROCK kinase-associated integrin signaling and receptors may be associated with cardiomyocyte maturation, physiological function, proliferation and apoptosis, which has not been examined in depth in the present study, cannot be ruled out (37,38).…”
Section: Discussionmentioning
confidence: 83%
“…Recently, Yan et al (36) demonstrated that the application of Y27632 promoted the gene expression of matrix metalloproteinases 2/3 and Notch-1 signaling to modulate Yes-associated protein-1 localization in the regulation of efficient patterning of cardiovascular spheroids following mesoderm formation from hPSC. Therefore, the possibility that ROCK kinase-associated integrin signaling and receptors may be associated with cardiomyocyte maturation, physiological function, proliferation and apoptosis, which has not been examined in depth in the present study, cannot be ruled out (37,38).…”
Section: Discussionmentioning
confidence: 83%
“…2 ). Of note, we have previously established the specificity of the anti-AT 2 antibody used in this study by Western blot/immunoprecipitation [ 23 , 24 , 36 ] and immunohistochemistry [ 12 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…e establishment of the RhoA/p38MAPK signal transduction pathway provides the basis and method for preventing and treating cardiovascular and cerebrovascular diseases caused by various stress responses [32,33]. RhoA/ ROCK pathway mediates high glucose-induced cardiomyocyte apoptosis via oxidative stress, JNK, and p38MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%